Evaluation of Spirulina platensis in Bicarbonate- Based Integrated Carbon Capture and Algae Production System utilizing different culture media - Christelle Paula Cortez Batac; Nadeine San Juan Gathercole; Ana Katrina Fajardo Maravilla; Arnel Bas Beltran (ASEAN Journal of Chemical Engineering, 2020)
A method known as Bicarbonate-based Integrated Carbon Capture andAlgae Production System (BICCAPS), is a growing study introduced as an alternative to current carbon capture and sequestration (CCS) methods. It is a closed-loop cycle involving inorganic carbon in the form of bicarbonates, which is consumed by microalgae for growth and utilizes the regenerated carbonates for another cycle of carbon capture. Existing literature requires more in-depth experimentation and analysis with regards to the viability of different microorganisms to the rising method. Spirulina platensis was evaluated in BICCAPS using 0.1M Na2CO3, employing three different culture media for growth, namely, modified Zarrouk’s, NPK- based, and NPK- based with A5 solution media. Biomass growth, productivity, and carbon dioxide utilization were investigated to determine the effectivity of BICCAPS as a carbon sequestration technique. At control conditions, NPK-based with A5 solution medium yielded the highest productivity with a value of 10.81 mg L-1 day-1. Likewise, using NaHCO3 as a carbon source, results show that the highest productivity was achieved also under NPK- based with A5 solution medium with a value of 6.80 mg L-1 day-1, as well as a high carbon conversion value of 2.092 day-1.